Skull base primary ewing sarcoma: A radiological experience of a rare disease in an atypical location - Mohd Syafiek Abdul Haq Saifuddin; Chiak Yot Ng; Mohd Shafie Abdullah (International Scientific Information, Inc., 2021)
Ewing sarcoma and primitive neuroectodermal tumor (PNET) are rare tumors that are grouped under the Ewing sarcoma family of tumors. These 2 tumors are prone to occur in pediatric patients and have highly malignant features [1]. Ewing sarcoma and PNET are also known as small round blue cell tumors because they share close histological similarities and overlapping radiological changes with other tumors such as neuroepithelioma, Askin tumor, and neuroblastoma [2]. These highly malignant tumors tend to occur in a pediatric and young adult age group and predominantly involve the bones. The incidence of skull bone Ewing sarcoma accounts for only 1% of all Ewing sarcomas [3], and primary skull base Ewing sarcoma occurs in less than 1% of cases [4]. We share our experience in this report of this rare case of skull base Ewing sarcoma and the management challenges we encountered in our center.